THE DIFFERENCES OF STUDENTS’ LEARNING ACHIVEMENT TAUGHT SOMATIC, AUDIOTORYTORY, VISUAL, AND INTELLECTUAL (SAVI) LEARNING MODEL AND DIRECTT INSTRUCTION (DI) LEARNING MODEL ON SETS TOPICS IN VII GRADE AT SMP N 1 BINJAI ACADEMIC YEAR 2014/2015 - Evridya . Rizki; Pargaulan . Siagian (Universitas Negeri Medan, 2015)
th: 0px;